2016
DOI: 10.5539/mas.v10n5p67
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption of Rhodamine B in Water by Modified Zeolites

Abstract: In this study, modified zeolites were prepared through the modification of raw zeolites, using hydrochloric acid (HCl) and cetyl trimethyl ammonium bromide (CTAB), whose properties were then characterized by a Zeta Potential Meter and an X-ray diffractometer. Also, the adsorption mechanisms were investigated in depth. The experimental results indicated that, in terms of the adsorption capacity of Rhodamine B in water, the modified zeolites were more favorable than the raw zeolites. As the dosage of adsorbent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The modified zeolites (HCl and cetyl trimethyl ammonium bromide) had a higher adsorption capacity than the unmodified zeolite [148]. The adsorption data followed Freundlich model and pseudo-second-order kinetic model.…”
Section: Amphoteric Dye Rhodamine B Zeolitementioning
confidence: 92%
“…The modified zeolites (HCl and cetyl trimethyl ammonium bromide) had a higher adsorption capacity than the unmodified zeolite [148]. The adsorption data followed Freundlich model and pseudo-second-order kinetic model.…”
Section: Amphoteric Dye Rhodamine B Zeolitementioning
confidence: 92%
“…IIayaraja et al (2013) found that the percentage removal of RB dye using activated carbon decreased from 86.9 % to 52.8 % with an increase in concentration of dye from 20 -100 mg/l. Wang et al (2016) reported that the removal percentage of RB dye on modified zeolities decreased from 93 % to 85% with the increase of initial dye concentration which the adsorption capacity of RB increased. Akash 2013found that the percentage of removal of RB dye on activated Mahua seed carbon (AMC) and activated neem seed carbon (ANC) decreased with the increase of dye concentration (50-100-150) ppm from 92% t0 83% to AMC and from 82% t0 64% to ANC.…”
Section: Effect Of Initial Rb Dye Concentrationmentioning
confidence: 98%